The Physical and Magnetic Properties of Sengon (Falcataria moluccana Miq.) Impregnated with Synthesized Magnetite Nanoparticles - Saviska Luqyana Fadia; Istie Sekartining Rahayu; Deded Sarip Nawawi; Rohmat Ismail; Esti Prihatini (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Sengon is one of the fast-growing wood that dominates Indonesian plantation forests and has been used as industrial raw material, fuel, and construction material. To enhance the physical characteristics of sengon wood, it needs technology of wood quality improvement, such as impregnation method by using Fe3O4 nanoparticles. Beside to enhance the quality of sengon wood, this technology can also expand the utilization of fast-growing wood. The presented research aims to examine the effects on physical and magnetic properties of sengon wood after being treated by magnetite nanoparticles impregnation. Magnetite nanoparticles were prepared by coprecipitation method with a precursor solution of iron ions mixture and weak base (NH4OH). The treatments of the magnetic wood consisted of 3 different concentrations that is untreated, 1% and 5% magnetite nanoparticles impregnation solution with demineralized water as a dispersant. Dimensional stability parameters, such as weight percentage growth, bulking impact, and effectiveness against swelling are increasing along the increase of concentration. Characterization tests such as SEM–EDX analysis showed the existence of Fe deposition in the wood cell membranes and pores of the wood. XRD analysis showed the appearance of magnetic peaks in the diffractogram in accordance with the decreased of crystallinity while the concentration increased and FTIR analysis showed Fe-O functional groups. Sengon wood magnetic was identified based on the VSM study, as a superparamagnetic components with mild magnetic characteristics.